Visible to Mid-infrared Waveband Photodetector Based on Insulator Capped Asymmetry Black Phosphorous - Han, Qi; Jiang, Yadong; Han, Jiayue; Dong, Xiang; Gou, Jun (Frontiers in Physics, 2021)
Processing layer dependent direct band gap and good absorption coefficient especially in mid-infrared band, black phosphorous is believed to make superior contribution than graphene in broadband photodetectors. The narrow band gap of 0.3eV for bulk black phosphorous helps absorbing infrared radiation while a relatively large dark current under zero gate voltage is inevitable. Few layer black phosphorous sheet with asymmetrical thickness sealed in insulator for protection is designed and explored for photosensitive mechanism in this work. Saturable absorption dominates the light harvesting process in visible light detection and thus limits maximum photocurrent to 3.3μA and 1.4μA for 520nm and 650nm lasers with a dark current of 0.7μA. While in near-infrared wavelength, a responsivity of 0.12A/W is inducted for 808nm free of adsorption saturation even if the incident power is increased to 200mW/cm^2. Discrimination for the origin of the photo-response in short wavelength is conducted and the abnormal negative and nearly constant photocurrent in mid-infrared, irrelevant to inhomogeneous thickness, reveals the photothermal effect in black phosphorous sheet. This work unravels various photoelectric features in black phosphorous and paves the way to designing more outstanding broadband photodetectors based on black phosphorous.